Cry of the wild : eight animals under siege - Foster, Charles, 1962- (Doubleday, an imprint of Transworld Publishers, 2023)
"A fox, grown strong on pepperoni pizza from the dustbins of the East End, dances along a railway track towards Essex, the territory of wild foxes and wilder huntsmen. An orca, mourning the loss of her mother in a valley west of Skye, knows that she must now lead the pod as matriarch. She swims again through her childhood, thinking about the old ways, the old roads, laid down thousands of years ago. But the old roads aren't so easy now. At moonrise in a West Country river, an otter floats slowly downstream. The tide, though it pushes him landwards when it exhales, seems to pull him out when it inhales. He turns on his back. He can see the stars clearly for the first time and wonders if he can swim to them. The land has never stopped waiting. It has only ever been in exile, right under our noses, waiting to confound, outrage and re-enchant"--